Productivity improvement through lean tools in cement industry – A case study - Md. Tanjid Hossen Irfan; Md. Rafiquzzaman; Yeasin Arafat Manik (Heliyon)
Cement is a vital commodity that accelerates economic growth and infrastructure development, compelling manufacturers to enhance productivity. Lean is a philosophy of increasing productivity while reducing waste and production losses in a manufacturing process. Many organizations benefit from lean adoption by increasing their productivity and efficiency. This study aims to examine the current production system of a cement industry where lean tools are underutilized and explores the potential for applying these tools to improve productivity. The current Overall Equipment Effectiveness (OEE) of the industry is almost 65.60 %, significantly below the world-class benchmark of 85 %. The study aims to identify the main causes of production loss or low OEE, including motor damage, bearing damage, vibration, and lack of 5S practice. It also tries to identify certain areas for improvement and makes recommendations on how to enhance them. Total Productive Maintenance (TPM) and 5S were used to decrease equipment failures and breakdowns, which resulted in an increase in OEE up to 68 %. These findings offer valuable insights for decision-makers to address root causes and enhance productivity.